APLIKASI KOMPOS LIMBAH KULIT BUAH KAKAO DAN JARAK TANAM BERBEDA TERHADAP PERTUMBUHAN TANAMAN TERUBUK (Saccharum edule Hasskarl) - Ramadhani Chaniago; Darni Lamusu (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2018)
Cocoa fruit skin is a waste that can cause environmental problems around the plantation. One way to utilize the waste of cocoa fruit skin is made organic fertilizer. The use of different spacing will affect the large number of plant unity area and will indirectly affect the absorption of nutrients, water and other growth factors. The purpose of this study was to determine the effect of composting of cocoa fruit skin waste on the growth of cropped plants (Saccharum edule Hasskarl) with different plant spacing. This field experiment was conducted from July to November 2016 with research location in Kecamatan Luwuk Banggai Regency. The experimental design used was factorial in randomized block design with 2 replications, then there were 18 treatment combinations. In this research the first factor of composition of cocoa fruit skin with cow dung consisting of 3 levels namely: P1 = 50 kg of compost: 10 kg of cow dung; P2 = 50 kg: 30 kg; P3 = 50 kg: 50. While the second factor are plant spacing consisting of 3 levels, namely: J1 = 100 cm X 150 cm; J2 = 100 cm X 100 cm; J3 = 100 cm X 50 cm. Based on the result obtained, It showed that the treatment of 50 kg of cocoa fruit skin compost with 50 kg of cow dung (P3) gave the best shoot effect on 5 weeks after planting (WAP) , to the best plant height that is P2 treatment on 3 (WAP), and the best leaf length is P2 treatment on 2 up to 4(WAP).Key words : Compost, Plant Spacing, Terubuk